Thermal analysis using induction and concentrated solar radiation for the heating of metals - Armando Rojas-Morín; Yolanda Flores-Salgado; Omar Alvarez-Brito; Alejandro Jaramillo-Mora; Arturo Barba-Pingarrón (Results in Engineering, 2022)
It is described the thermal analysis of a cylindrical workpiece involving the coupling of two heat sources. Induction heating was applied, which generated Eddy currents that circulated through the workpiece and heated the material surface. Also, concentrated solar energy heating was applied at the top of the workpiece, which generated a heat flux from the Fresnel lens concentrator. The formulation for the transient heat transfer analysis is presented. A numerical simulation for solving Maxwell's equations along with coupled and transient heat transfer conditions was developed using COMSOL Multiphysics®. The temperature distribution of the cylindrical workpiece was obtained, and the heating time was also determined. Subsequently, we compared this simulation and the experimental test. The experimental results show that for the coupling induction and concentrated solar energy, the temperature reaches its maximum faster than induction or concentrated solar energy alone. This kind of proposed alternative system can be useful for time and energy reduction for industrial heat treatments like annealing, precipitation hardening, quenching and tempering, isothermal treatments of ferrous and non-ferrous alloys.